Diskriminasi pada Pemain Game Online Perempuan - Brigietta Irna Pramesty (COMMUNICATION MAJOR, 2021)
Abstract Advances in technology have also developed entertainment facilities that are served to the community. One of the available entertainment facilities is mobile games or mobile games. Mobile games have considerable appeal for people of all ages and genders. This study analyzes the discrimination of female “Mobile Legends: Bang Bang” game players in the interaction of online game players Mobile Legend: Bang Bang. Research on gender discrimination focuses more on issues of work and gender roles in the cultural structure of society but still rarely researches leisure activities. For this reason, the study aims to determine the discrimination experienced by female players in Mobile Legends: Bang Bang and the forms of verbal discrimination spoken by the players during the game. This research was conducted using the phenomenological method to explore the experiences of the female players. The adventures of female players are used to understand the phenomena that lead to discrimination. The results of this study show that female players have experienced discrimination from male players. Discriminatory words and sentences indirectly degrade the degree and dignity of female players because they accuse female players of being prostitutes, being equated with animals, and mentioning that the Mobile Legend game is not a place for women. This research shows that gender discrimination occurs in the employment sector and in the entertainment sector, one of which is online games.Keywords: discrimination; interactive games; mobile games; Mobile Legends; woman players. Abstrak Kemajuan teknologi turut mengembangkan sarana hiburan yang disuguhkan untuk masyarakat. Salah satu sarana hiburan yang tersedia adalah permainan seluler atau mobile games. Mobile games memiliki daya tarik yang cukup besar bagi masyarakat dari berbagai kalangan usia maupun gender. Penelitian ini menganalisis diskriminasi pada pemain game “Mobile Legends: Bang Bang” perempuan pada interaksi pemain game online Mobile Legend:Bang Bang. Penelitian tentang diskriminasi gender lebih banyak berpusat pada persoalan pekerjaan dan peran gender dalam struktur budaya masyarakat, tetapi masih jarang meneliti pada kegiatan hiburan (leisure). Untuk itu, penelitian bertujuan untuk mengetahui diskriminasi yang dialami oleh pemain perempuan Mobile Legends: Bang Bang dan bentuk-bentuk diskriminasi verbal yang diucapkan oleh para pemain selama permainan berlangsung. Penelitian ini dilakukan dengan menggunakan metode fenomenologi untuk menggali pengalaman dari para pemain perempuan. Pengalaman dari pemain perempuan digunakan untuk memahami fenomena yang mengarah pada diskriminasi. Hasil penelitian ini memperlihatkan bahwa pemain perempuan pernah mengalami diskriminasi dari pemain laki-laki. Kata-kata dan kalimat diskriminatif dikemukakan dengam menyebut pemain perempuan sebagai pelacur, disamakan dengan binatang, dan menyebutkan bahwa permainan Mobile Legend bukan tempat bagi perempuan. Melalui penelitian ini, menunjukkan bahwa diskriminasi gender terjadi tidak hanya pada sektor pekerjaan, tetapi juga pada sektor hiburan, salah satunya pada permainan daring. Kata Kunci: diskriminasi; Mobile Legends; permainan interaktif; pemain perempuan.